Endomyocardial fibrosis of the right ventricle - Diego Sarre-Alvarez; Cuitláhuac Arroyo-Rodríguez; Juan Manuel Chino-Mendoza; Yhaquelina Admeli Quispe-Villca; Jose Antonio Arias-Godinez (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2019)
Endomyocardial fi brosis is a rare cause of restrictive cardiomyopathy which predominates in lowincome population living in tropical areas. It´s characterized by endomyocardial fi brous tissue deposition causing restrictive physiology with poor prognosis without proper management. We present a 40-yearold woman with right ventricular endomyocardial fi brosis complicated by pericardial effusion and a giant atrial thrombus. The use of multimodal imaging is very important for the diagnosis of this extremely rare pathology in our country.